Implementasi Fungsi Perencanaan KBIH Darul Ma’arif dalam Meningkatkan Pelayanan Jamaah - Sari Hasanah; Dewi Sadi'ah (Tadbir: Jurnal Manajemen Dakwah, 2021)
This study aims to determine how the implementation of the planning function in KBIH Darul Ma'arif. This study uses a descriptive method with a qualitative approach that aims to describe, explain, and explain data regarding the implementation of the planning function at KBIH Darul Ma'arif in improving the service levels of the congregation, namely through interviews, observation, documentation study of the research object. The results showed that, the implementation of the planning function in KBIH Darul Ma'arif in improving the services of the congregation had fulfilled the needs of the prospective congregation, the determination of the objectives of the KBIH was to get satisfaction, calm and perfection in performing the pilgrimage. The determination of the KBIH program is to get excellent service with several programs: pre-hajj pilgrimage, hajj pilgrimage and post-hajj pilgrimage. Determining the KBIH schedule, namely always determining the day and date, time, guidance and material so as to provide good service to the pilgrims. Keywords: Implementation; Planning function; KBIH; Jamaah service